Pengaruh Profitabilitas, Non Performing Loan, Suku Bunga Terhadap Harga Saham - Anisa Ramdaniah; Diyan Lestari (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the effect of ROA, NPL, Interest Rate on Stock Price. The population in this study are banking companies listed in the Indonesia Stock Exchange (IDX) from 2018-2020. The sample selection method used purposive sampling method and obtained the number of research samples as many as 19 companies with a total of 209 observational data. The data analysis method used in this study was panel regression analysis using Eviews version 9. The results showed that partially ROA affect the Stock Price, NPL do not affect the Stock Price, while Interest Rate affect the Stock Price.